Analysis of Speech Acts in Natasha Berg’s Presentation on ChatGPT: A Pragmatic Examination Drawing From Searle and Yule’s Theory - Dian Quini Handayani Ernanto Putri; Dina Destari; Anis Komariah (El-Syaker : Samarinda International Journal of Language Studies, 2024)
As social beings who depend on the relationships of others, human needs communication. In social interactions, not least in education, language is primarily used as a tool. Individuals who experience language difficulties will have difficulty in conveying their thoughts or ideas to others.  As a result, communication becomes less than optimal and sometimes fails. In this case, communication is not just a matter of one-way message delivery, but also involves the exchange of mutually understood contexts so that two-way communication occurs. To get the context of communication and become a competent communicator, pragmatics is necessary and one of the crucial ideas in pragmatics is the concept of speech acts. This research was conducted with the aim of knowing the illocutionary speech acts and knowing the most frequently used acts contained in Natasha Berg's speech about ChatGPT using Searle and Yule's theory. This research used qualitative approach and content analysis as a research method. Following the analysis of illocutionary act of Natasha Berg's speech, the results presented that they were 62 speech utterances contained illocutionary acts. They were thirty-five assertives (56,45%), ten directives (16.12%), nine commisive (14.51%), seven expressive (11.29%) and one declarative (1.61%). The findings indicated that assertive was the most frequently seen illocutionary act during the speech since it provided the audience with factual information related to the facts of the use of ChatGPT in the school environment and its implications for students based on study and also field facts. By analyzing the illocutionary act, accurate communication and comprehension of the aim or purpose can be learned, enabling the intended outcome of communication to be achieved.